2016
DOI: 10.1631/jzus.b1500322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic hepatectomy, percutaneous radiofrequency ablation and open hepatectomy in the treatment of small hepatocellular carcinoma

Abstract: Abstract:Objective: Three mainstream techniques-laparoscopic hepatectomy (LH), percutaneous radiofrequency ablation (pRFA), and open hepatectomy (OH)-were compared in this study, in terms of their efficacies in the treatment of small hepatocellular carcinoma (HCC). Methods: A comparative study was performed within a total of 94 patients diagnosed with small HCC in our hospital from 2005 to 2010, who underwent LH (28), RFA (33), or OH (33). They had either a single tumor lesion of less than 5 cm or up to three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…We estimated the volume of hospitals where studies were performed. Some institutes were noticeably very high-volume centers with almost 3000 cases in 6 years [ 39 ], while others performed as few as 60 procedures in 5 years [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the volume of hospitals where studies were performed. Some institutes were noticeably very high-volume centers with almost 3000 cases in 6 years [ 39 ], while others performed as few as 60 procedures in 5 years [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Through the preliminary search, 990 articles are obtained. After reading titles and abstracts and full texts and removing duplicate documents, 47 articles were included in our study, which involved 5889 patients (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The safety and feasibility of laparoscopic hepatectomy have been reported by many previous series. 14,21,23,24,26 From controversy to acceptance, LH has developed over the last 20 years in terms of technological innovations, improvements in surgical techniques, and accumulation of experience by surgeons. In this series, we reviewed the development of LH and its current status.…”
Section: Discussionmentioning
confidence: 99%
“…The sample sizes varied from 46 to 156 patients. Five studies [10,[18][19][20][21] were conducted in China. The mean age of patients varied from 48 to 73 years old.…”
Section: Characteristics Of Included Rctsmentioning
confidence: 99%
“…Although surgery provides the best option for patients with hepatic tumors, less than 30% of patients with HCC have an opportunity to undergo surgery [8]. Previous studies [9][10][11] have demonstrated that local ablation, especially radiofrequency ablation (RFA), can also achieve radical cure effects on HCC, and its short-and long-term survival rates are comparable and even similar to surgery strategies. In addition, RFA treatment has the advantages of mild trauma, low risk of bleeding, and high reproducibility compared with surgery.…”
Section: Introductionmentioning
confidence: 99%